Cartography of the mechanical properties of the human amniotic membrane. (November 2019) - Grémare, Agathe; Jean-Gilles, Sarah; Musqui, Pauline; Magnan, Laure; Torres, Yoann; Fénelon, Mathilde; Brun, Stéphanie; Fricain, Jean-Christophe; L'Heureux, Nicolas
Abstract: Because of its low immunogenicity, biological properties, and high availability, the Human Amniotic Membrane (HAM) is widely used in the clinic and in tissue engineering research. However, while its biological characteristics are well described, its mechanical properties remain understudied especially in terms of inter- and intra-HAM variability. To guide bioengineers in the use of this natural biomaterial, a detailed cartography of the HAM's mechanical properties was performed. Maximal force (Fmax) and strain at break (Smax) were identified as the relevant mechanical criteria for this study after a combined analysis of histological sections, thickness measurements after dehydration, and uniaxial tensile tests. Eight HAMs were studied by mechanical cartography using a standardized cutting protocol and sampling pattern. On average, 103 ± 10 samples were retrieved and tested per HAM. Intra-tissue variability highlighted the fact that there were two mechanically distinct areas (placental and peripheral) in each HAM. For all HAMs, placental HAM was significantly stronger by 82 ± 45% and more stretchable by 19 ± 6% than their peripheral counterparts. Our results also demonstrated that placental, but not peripheral, HAM presented isotropic mechanical properties. Thus, placental HAM can be a raw material of choice that could be favored especially in the development of tissue engineering products where mechanical properties play a key role. Graphical abstract: Image 1 Highlights: Placental HAM was stronger and more stretchable than peripheral. Placental HAM presented isotropic mechanical properties. Intra-tissue variability was higher than inter-tissue variability.